Functional recoverability post-pyeloplasty in children with ureteropelvic junction obstruction and poorly functioning kidneys: Systematic review. Issue 5 (October 2022) - Abbas, Tariq; Elifranji, Mohammed; Al-Salihi, Muthana; Ahmad, Jamil; Vallasciani, Santiago; Elkadhi, Abderrahman; Özcan, Cihat; Burgu, Berk; Akinci, Aykut; Alnaimi, Abdulla; Salle, J.L. Pippi
Summary: Background: The management of poorly functioning kidneys (PFK) associated with ureteropelvic junction obstruction (UPJO) is controversial. There is contradictory information about how to best manage these cases: pyeloplasty or nephrectomy? Objective: To systematically summarize the available evidence concerning the effects of pyeloplasty on the differential renal function of PFK in children with unilateral UPJO, highlighting the ongoing challenges in their definition, management, and long-term follow-up. In addition, we aim to verify potential predictors of renal functional recoverability that could help clinicians choose candidates for pyeloplasty. Methods: We searched several databases including PubMed, Embase, and Cochrane Library CENTRAL until August 20, 2021, according to the PRISMA guidelines. The following concepts were searched: pediatric, ureteropelvic junction obstruction, UPJO, pyeloplasty, recovery, split renal function, and differential renal function. We enrolled studies where the PFK was defined as preoperative differential renal function (DRF) ≤30% by renal scintigraphy. Potential predictors of renal functional recoverability were assessed and compared among studies. The quality of the included studies was evaluated using a modified version of the Newcastle–Ottawa scale (NOS). Results: 1499 citations perceived as relevant to screening were retrieved. After screening, 20 studies were included, comprising a total of 625 cases. The number of patients in each study varied between 5 and 84, while the average post-surgical follow-up duration ranged between 3 months and 180 months. The most significant preoperative predictive factor for postoperative functional recoverability was the baseline DRF, especially when antenatally diagnosed. The quality was considered average in a significant portion of included studies. Conclusion: A significant proportion of PFK showed an increase of DRF post-pyeloplasty. However, no consistent predictive factors for functional recoverability have yet been determined apart from preoperative DRF. Until further evidence appears, pyeloplasty should be considered a valid option in the armamentarium of UPJO management in PFK.